Potato Organic Farming in Batu City, Indonesia - Sugiarto Sugiarto; Rudi Sulistiono; Sudiarso Sudiarso; Soemarno Soemarno (Program Pascasarjana Universitas Brawijaya, 2013)
Organic potato cultivation was an effort to improve declining quality of potato agroecosystems and to preserve soil fertility. This study was conducted to analyze pattern of farming system and land management on the area of organic potatoes in Batu city. Research was conducted by the survey method, respondents were determined by the method of stratified cluster sampling. Farmer respondents were experienced organic potato farmer and as